The Hiphive Package for the Extraction of High‐Order Force Constants by Machine Learning. Issue 5 (11th February 2019) - Eriksson, Fredrik; Fransson, Erik; Erhart, Paul
Abstract: The efficient extraction of force constants (FCs) is crucial for the analysis of many thermodynamic materials properties. Approaches based on the systematic enumeration of finite differences scale poorly with system size and can rarely extend beyond third order when input data is obtained from first‐principles calculations. Methods based on parameter fitting in the spirit of interatomic potentials, on the other hand, can extract FC parameters from semi‐random configurations of high information density and advanced regularized regression methods can recover physical solutions from a limited amount of data. Here, thehiphive Python package, that enables the construction of force constant models up to arbitrary order is presented.hiphive exploits crystal symmetries to reduce the number of free parameters and then employs advanced machine learning algorithms to extract the force constants. Depending on the problem at hand, both over and underdetermined systems are handled efficiently. The FCs can be subsequently analyzed directly and or be used to carry out, for example, molecular dynamics simulations. The utility of this approach is demonstrated via several examples including ideal and defective monolayers of MoS2 as well as bulk nickel. Abstract : The hiphive package is a powerful tool for the efficient extraction of high‐order force constants. It thereby enables modeling the thermodynamic and vibrational properties of, for example, large, low‐symmetry systems and strongly anharmonic materials. This ultimately includes, for example, temperature‐dependent phonon dispersions, life times, and the thermal conductivity.